Homology modeling and docking study of Shewanella-like protein phosphatase involved in the development of ookinetes in Plasmodium - Sandhini Singh; Ruchi Yadav (Wolters Kluwer Medknow Publications, 2019)
Objective: Parasites of the genus Plasmodium cause a great deal of morbidity and mortality worldwide, largely in regions with limited access and indication to the tools necessary to control mosquito populations and to treat human infections of malaria. Five species of this class of eukaryotic pathogens cause different human diseases, with Plasmodium falciparum alone infecting approximately 500 million people per year and resulting in approximately one million deaths. Materials and Methods: The two genes encoding the Shewanella-like protein phosphatases of P. falciparum, SHLP1 and SHLP2, are conserved among members of Plasmodiidae family. SHLP is frequently found in asexual blood stages and expressed at all stages of the life cycle of parasite. SHLP deletion results in a reduction in microneme formation, ookinetes (zygote) development, and complete ablation of oocyst formation, thereby blocking transmission of parasite. Structure modeling of SHLP protein can be helpful in understanding the active site and binding site information and hence can be used for drug designing and for therapeutics against malaria. Study of SHLP and its variants was carried out using UniProtKB database. Homology modeling was performed using Schrödinger software, and the modeled structure was verified using Ramachandran plot. Ten antioxidants were searched in PubChem database for docking and comparative analysis. Docking was carried out against SHLP-modeled protein, and the ligand-protein interaction map was analyzed. Effective role of resveratrol was studied against SHLP protein using docking method to identify protein-ligand interaction scheme and bond formation. Results: SHLP protein was modeled and docking was carried out to identify the binding sites and interaction with the SHLP protein. Docking study suggested that resveratrol has a strong interaction with SHLP protein and can be used as a potential ligand for drug designing. Conclusion: SHLP plays a crucial role in ookinetes and microneme development in Plasmodium; hence ligand, which can interact and inhibit SHLP protein, can be a potential drug against malarial parasite development. We studied the binding of antioxidant, such as resveratrol, with this protein-using docking method and it was found that resveratrol as an antioxidant can bind with the target SHLP protein.